Emma Kay: Fodder and Drincan: Anglo-Saxon Culinary History - Crowden, James (Petits Propos Culinaires, 2023)
Emma Kay: Fodder and Drincan: Anglo-Saxon Culinary History: Prospect Books, 2022: 224 pp., paperback, £20.00.